(untitled) (TSUL LEGAL REPORT, 2026)
The article examines the complex civil-law regulation of digital and physical objects created through additive manufacturing technologies. Drawing on comparative analysis of the Uzbek Civil Code, the Laws on Copyright, Patents, and E-Commerce, and strategic documents such as the Strategy “Uzbekistan – 2030” and Digital Uzbekistan–2030, the study identifies significant legal gaps in defining ownership, authorship, and liability concerning 3D-printed objects and their digital design files (CAD models). The article contrasts Uzbekistan’s framework with the approaches of the EU, USA, China, Germany, France, and post-Soviet jurisdictions, emphasizing how most countries rely on adapting existing property and intellectual property doctrines rather than introducing a new regulatory regime. The analysis highlights unresolved doctrinal issues such as the dual nature of 3D-printed property (digital and material), uncertainty of rights transfer in digital environments, and insufficient enforcement mechanisms for online infringements. Finally, the author proposes sui generis reforms within Uzbekistan’s civil law – clarifying digital goods ownership, expanding copyright scope to CAD files, introducing limited-use exceptions, and strengthening IP enforcement online – aligning national legislation with international best practice and the technological goals of Strategy 2030.